1954
DOI: 10.1143/ptp.12.156
|View full text |Cite
|
Sign up to set email alerts
|

On the Construction of Potential in Field Theory

Abstract: The general formal construction of potential in the field theory is given. It is constructed so as to conserve the normalization of the wave function, irrespective of the switch-off or -on of the potential. The potential is anaiyzed into its normal part and probability operator. The probability operator is shown to be related to the probability of the system staying in the same state as it does when the interaction is switched off.From the probability character of the probability operator, we can get a measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

1956
1956
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(49 citation statements)
references
References 0 publications
0
49
0
Order By: Relevance
“…It was found that this interaction, also obtained on a different basis in earlier works [15], involved a renormalization of the so-called instantaneous approximation. For small couplings, the renormalization factor is given by the probability of the system being in a two-body component, without accompanying bosons in flight.…”
Section: Introductionmentioning
confidence: 52%
“…It was found that this interaction, also obtained on a different basis in earlier works [15], involved a renormalization of the so-called instantaneous approximation. For small couplings, the renormalization factor is given by the probability of the system being in a two-body component, without accompanying bosons in flight.…”
Section: Introductionmentioning
confidence: 52%
“…Note that this is not a unique separation of the two branch cuts. To make closer contact with previous work [16,17] we can rewrite Eq. (14) in a form closer to the (E − E ′ ) prescription:…”
Section: Initial-state Interactionmentioning
confidence: 90%
“…For this purpose we are guided by the unitarity transformation method of Ref. [16,17]. This method is one way to isolate the different singularities of a particular diagram.…”
Section: Initial-state Interactionmentioning
confidence: 99%
“…In Ref. [8], chiral power counting was applied to derive nuclear forces from the most general effective chiral Lagrangian for pions and nucleons by eliminating the pionic Fock-space components via the FST-Okubo projection method [9,10]. The two-pion exchange diagrams relevant for the discussion of the properties of nuclear matter are shown in Fig.…”
Section: The Methodsmentioning
confidence: 99%